Detection of epileptic activity in absence of EEG interictal epileptic discharges. Issue 3 (March 2016) - Pittau, F.; Genetti, M.; Birot, G.; Tomescu, M.; Baldini, S.; Vulliémoz, S.; Michel, C.; Seeck, M.
Abstract : Aim: To assess if the EEGs of epileptic patients without any detectable spikes contain the voltage specific epileptic map. Methods: Fifteen patients with pharmaco-resistant focal epilepsy were included. Six minutes of resting state EEG with and without any detectable spikes were selected from long-term recording (31-channels, ref:FCz). Resting-state EEGs from 48 healthy control-subjects were also recorded. For each patient EEG, we calculated the averaged spike and its voltage map. We fitted the spike map on (i) EEG of patient with visible spikes (ii) EEG of the same patient without any visible spike and (iii) EEGs of the 48 controls. The presence of the voltage epileptic map was characterized by: mean-correlation and Global Explained Variance (GEV). For these criteria statistical differences between (1) controls and EEG with spikes, and (2) controls and EEG without spikes were evaluated. Results: The patient-specific epileptic voltage map was significantly more represented in the spike-free EEGs of patients than in EEGs of healthy controls (GEV p = 0.029; mean-correlation p = 0.032). This difference was more accentuated for patient-EEGs containing spikes (GEV p = 0.001, mean-correlation p < 0.001). Discussion: Scalp EEGs of pharmaco-resistant epilepsy patients contains the epileptic voltage map (index of epileptic activity), even in absence of any detectable interictal epileptic discharges.